Lactic acid fermentation of food waste as storage method prior to biohydrogen production: Effect of storage temperature on biohydrogen potential and microbial communities. (June 2023) - Roslan, Eqwan; Magdalena, Jose Antonio; Mohamed, Hassan; Akhiar, Afifi; Shamsuddin, Abd Halim; Carrere, Hélène; Trably, Eric
Graphical abstract: Highlights: Ethanol accumulated at 10 °C, 23 °C whilst lactate outstood at 4 °C, 35 °C–55 °C. LAF as storage has no negative impact on BHP, averaging at 94.6 ± 25.1 mL/gVS. LAF as storage improved DF maximum hydrogen production rate by at least 57%. Indigenous HPB Clostridium sp. emerged even after 15 days of LAF storage. LAB Lactobacillus sp. and HPB Clostridium sp. co-existed in dark fermentation. Abstract: This study aims to investigate the impact of utilizing lactic acid fermentation (LAF) as storage method of food waste (FW) prior to dark fermentation (DF). LAF of FW was carried out in batches at six temperatures (4 °C, 10 °C, 23 °C, 35 °C, 45 °C, and 55 °C) for 15 days followed by biological hydrogen potential (BHP) tests. Different storage temperatures resulted in different metabolites distribution, with either lactate or ethanol being dominant (159.2 ± 20.6 mM and 234.4 ± 38.2 mM respectively), but no negative impact on BHP (averaging at 94.6 ± 25.1 mL/gVS). Maximum hydrogen production rate for stored FW improved by at least 57%. Microbial analysis showed dominance of lactic acid bacteria (LAB) namely Lactobacillus sp., Lactococcus sp., Weisella sp., Streptococcus sp. and Bacillus sp. after LAF. Clostridium sp. emerged after DF, co-existing with LAB. Coupling LAF as a storage method was demonstrated as a novel strategy of FW management for DF, for a wide range of temperatures.